2022
DOI: 10.1002/aac2.12049
|View full text |Cite
|
Sign up to set email alerts
|

Another wrinkle with age: Aged collagen and intra‐peritoneal metastasis of ovarian cancer

Abstract: Background: Age is the most significant risk factor for ovarian cancer (OvCa), the deadliest gynecologic malignancy. Metastasizing OvCa cells adhere to the omentum, a peritoneal structure rich in collagen, adipocytes, and immune cells. Ultrastructural changes in the omentum and the omental collagen matrix with aging have not been evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…AGEs crosslink collagen and have been shown to block collagenolysis [ 7 ]. We have previously observed an increase in AGE content in isolated aged murine tail collagen relative to collagen from young mice, but omental collagen has not yet been investigated [ 5 ]. To examine AGE content in the intact omental tissue, second harmonic generation (SHG) imaging in conjunction with 2-photon excitation fluorescence (TPEF) microscopy using anti-AGE antibodies was employed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…AGEs crosslink collagen and have been shown to block collagenolysis [ 7 ]. We have previously observed an increase in AGE content in isolated aged murine tail collagen relative to collagen from young mice, but omental collagen has not yet been investigated [ 5 ]. To examine AGE content in the intact omental tissue, second harmonic generation (SHG) imaging in conjunction with 2-photon excitation fluorescence (TPEF) microscopy using anti-AGE antibodies was employed.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that omental collagen from aged mice displayed significantly enhanced anisotropy with an increase in long linear fibers and thick banding relative to omenta from young mice [ 5 ], and similar results are seen in Figure 1 a. To evaluate the potential impact of AGE breakers on omental ultrastructure and function, young (Y, 3–6 month) or aged (A, 20–23 month) mice were placed into one of four cohorts ( Figure 2 a): young + vehicle control, aged + vehicle control, aged + ALT-711, or aged + 2C8.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations